Masalah Sosial dalam Novel Surga Anjing Liar karya Adimas Immanuel - Yetriani Yetriani; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The purpose of this study is to describe the forms of social problems, the causes of social problems, the impact of social problems contained in Adimas Immanuel’s Surga Anjing Liar novel. The subject of this research is Adimas Immanuel’s Surga Anjing Liar novel, published in 2020. This research is a type of literary research the uses a descriptive method. The research instrument is the researcher who uses instrument tools in the from of recording sheet and data analysis. The result of the study are the form of social problems include; poverty, crime, family disorganization, war, violation of societal norm, environmental and bereaucratic problems, factors that cause social problem are caused by economic, biological, and psychological factors, the impact of social problems can be in the form of increased crime, gap between people rich dan poor, group divisions, emergence of deviant behavior dan rising unemployment.